Dispersal behaviour of Euwallacea nr. fornicatus (Coleoptera: Curculionidae: Scolytinae) in avocado groves and estimation of lure sampling range. (24th January 2019) - Owens, David; Seo, Meeja; Montgomery, Wayne S.; Rivera, Monique J.; Stelinski, Lukasz L.; Kendra, Paul E.
Abstract: Invasive ambrosia beetles in the Euwallacea nr. fornicatus species complex (Coleoptera: Curculionidae: Scolytinae) threaten avocado production in multiple countries. These pests are currently monitored with lures containing quercivorol; α‐copaene was also recently discovered to be an effective attractant. We investigated dispersal behaviour of female E . nr . fornicatus in two Florida avocado groves using mark–release–recapture experiments and laboratory flight mills. Additionally, we estimated the sampling range of quercivorol and α‐copaene lures deployed alone and in tandem. The two‐component lure recaptured 31.2% of marked beetles, which was significantly more than quercivorol (11.2%) or α‐copaene (8.8%) alone. Contour analysis indicated that wind speed and direction can influence the number of females that disperse, as well as the direction and distance of their flight. Two methods were used to estimate sampling range and both of them indicated comparable effective ranges for the three lure treatments, with 80% of marked beetles being recaptured within 30–35 m of the release point. Average total flight distance in laboratory tests was 81.0 m in 24 h, with a maximum distance recorded at 400 m. The combination of quercivorol and α‐copaene lures provides the best detection of pest E . nr. fornicatus in Florida, with a recommended trap spacing of approximately 30 m in surveillance programmes for this pest in avocado groves.